2018
DOI: 10.4012/dmj.2016-234
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage and penetration depth of different fissure sealant materials after cyclic thermo-mechanic and brushing simulation

Abstract: The aim of the study was to evaluate microleakage and the penetration-depths of different fissure-sealant materials applied with/ without enameloplasty after cyclic aging. One-hundred-sixty mandibular molars were divided into non-invasive and enameloplasty preparation groups and eight material subgroups, including: flowable composites (microhyrid, nanohybrid, and nanofilled), three resin-based (unfilled, filled, and highly-filled), a giomer-based, and a glass-ionomer-based fissure sealant. Specimens were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
8
0
3
Order By: Relevance
“…While there were many studies assessing microleakage of pit and fissure sealants [22][23][24] , to our knowledge no study was available regarding the microleakage of sealants in relation to different etching times. When analyzing the present data, it can be concluded that the mean values obtained were generally low, which is also consistent with most recently published data on resin-based fissure sealants 25) . Nevertheless, the present investigation recorded another non-significant trend in aprismatic enamel: In our study, it was observed that 60 s etching resulted in a lower dye penetration compared to that with 15 s etching (0.6% vs. 3.0%).…”
Section: Discussionsupporting
confidence: 92%
“…While there were many studies assessing microleakage of pit and fissure sealants [22][23][24] , to our knowledge no study was available regarding the microleakage of sealants in relation to different etching times. When analyzing the present data, it can be concluded that the mean values obtained were generally low, which is also consistent with most recently published data on resin-based fissure sealants 25) . Nevertheless, the present investigation recorded another non-significant trend in aprismatic enamel: In our study, it was observed that 60 s etching resulted in a lower dye penetration compared to that with 15 s etching (0.6% vs. 3.0%).…”
Section: Discussionsupporting
confidence: 92%
“…Resin, glass ionomer, polyacid-modified resin, and more recently giomer-based fissure sealants are the material groups capable of use for sealing. 18,19 The clinical success of sealants depends on the materials’ ability to adhere to the enamel surface. The sealant adhesion ability can be measured using the SBS test.…”
Section: Discussionmentioning
confidence: 99%
“…Quader et al 27 reported that giomer possessed greater compressive strength and toughness than glass ionomer. The majority of previous studies have assessed the F-releasing, penetration depth, and microleakage values of the giomer-based fissure sealant, 19,28 and very few have evaluated its SBS.…”
Section: Discussionmentioning
confidence: 99%
“…La microfiltración es la que perjudica al factor de fallo de adherencia entre el sellador y el armazón del diente y puede ser determinada por muchos técnicas in vitro. Con las ventajas de la fiabilidad, simplicidad y facilidad de aplicación, la penetración del colorante es un método bien establecido y comúnmente utilizado para la determinación de microinfiltración in vitro (17) . Es definida como el paso indetectable(clínicamente) de bacterias, fluidos, moléculas o iones entre las paredes de la cavidad y el material restaurativo aplicado, como resultado de diferencias en el coeficiente de expansión térmica de material y el tejido dentario o por contracción promovida durante la polimerización (18) .…”
Section: Microfiltraciónunclassified